RASIO TAJUK AKAR TANAMAN MELON (Cucumis melo L.) PADA MEDIA TANAM DAN KETERSEDIAAN AIR YANG BERBEDA - Rusmana . (Jurnal Agroekoteknologi, 2017)
The research was aimed to determine the response of root-shoot ratio of melon (Cucumis melo L.) on planting medium and different water availability. The research was conducted for three months starting from July until September 2017 at Greenhouse of Agriculture and Marine of Cilegon City. The experimental used Randomized Completely Design as factorial with 2 factors. The first factor was planting medium consisted of 3 levels ie 100 % soil medium, compost medium 100%, and soil medium + compost 1: 1. The second factor was water stress consisted of 4 levels ie without water stress, water stress interval every 3 days, water stress interval every 6 days, and water stress interval 9 days. The results showed that the root-shoot ratio was influenced by reduced water availability and medium planting. The longer the water delivery interval decreased the root-shoot ratio of melon.Keywords: Root-shoot ratio, Planting medium, Water deficit